2019
DOI: 10.1038/s41467-019-09598-9
|View full text |Cite
|
Sign up to set email alerts
|

The class 3 PI3K coordinates autophagy and mitochondrial lipid catabolism by controlling nuclear receptor PPARα

Abstract: The class 3 phosphoinositide 3-kinase (PI3K) is required for lysosomal degradation by autophagy and vesicular trafficking, assuring nutrient availability. Mitochondrial lipid catabolism is another energy source. Autophagy and mitochondrial metabolism are transcriptionally controlled by nutrient sensing nuclear receptors. However, the class 3 PI3K contribution to this regulation is unknown. We show that liver-specific inactivation of Vps15 , the essential regulatory subunit of the class 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 68 publications
(92 reference statements)
8
61
0
Order By: Relevance
“…Lysosomal inhibition leads to downregulation of PPARα and its target genes, decreasing peroxisomal lipid oxidation and biogenesis [250]. The class 3 PI3K, Vps15, which plays a central role in autophagy, has been shown to control PPARα activation for lipid degradation and mitochondrial biogenesis [251]. In hepatocytes, PPARα activation promotes lipoprotein TG hydrolysis by increasing the enzyme activity of lipoprotein lipase (LPL) through a direct increase in its transcription, and decreases the expression of genes encoding lipoproteins, such as apolipoprotein C3 and apolipoprotein A4, which act as inhibitors of LPL activity [220,225].…”
Section: Ppars In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Lysosomal inhibition leads to downregulation of PPARα and its target genes, decreasing peroxisomal lipid oxidation and biogenesis [250]. The class 3 PI3K, Vps15, which plays a central role in autophagy, has been shown to control PPARα activation for lipid degradation and mitochondrial biogenesis [251]. In hepatocytes, PPARα activation promotes lipoprotein TG hydrolysis by increasing the enzyme activity of lipoprotein lipase (LPL) through a direct increase in its transcription, and decreases the expression of genes encoding lipoproteins, such as apolipoprotein C3 and apolipoprotein A4, which act as inhibitors of LPL activity [220,225].…”
Section: Ppars In Glucose and Lipid Metabolismmentioning
confidence: 99%
“…Thus, the loss of autophagy leads to an over-accumulation of NCoR1, which then suppresses PPARα activity and results in further impairment of autophagy and lipid oxidation [9] ( Figure 1B). Another study further supported the role of autophagy on PPARα action showing that hepatic expression of the class 3 PI3K is essential for metabolic adaptation to starvation in the liver through the control of PPARα transcriptional activity [59]. This study showed that the loss of hepatic expression of class 3 PI3K/Vps15 effected the levels of PPARα ligands, as well as PGC1α and NCoR1 levels [59].…”
Section: Lysosomes Control Pparα Nuclear Actionmentioning
confidence: 57%
“…However, in autophagy deficient Vps15-deficient hepatocytes this process is impaired, leading to NCoR1 stabilization and inhibition of hepatic PPARα activity. [59]. Therefore, the authors proposed that the class 3 PI3K/VPS15 exerted a broad transcriptional control in the liver to match autophagic activity with mitochondrial metabolism during fasting, via regulation of nuclear receptor action [59].…”
Section: Lysosomes Control Pparα Nuclear Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/Akt deactivation was found to be also linked with mitochondria depolarization [53]. Mitochondrial biogenesis in hepatocytes required functional class 3 PI3K, which controls PPARα transcriptional activity and harmonizes energy demand with mitochondrial content [54]. Inhibition of PI3K was also found to disable the effect of PUR on mitochondrial homeostasis in nonalcoholic fatty liver disease [55].…”
mentioning
confidence: 99%